PENGARUH MODEL PEMBELAJARAN JIGSAW DISERTAI FLASHCARD TERHADAP HASIL BELAJAR SISWA PADA MATERI JAMUR - Saputri, Emilta; Ningsih, Kurnia; Yeni, Laili Fitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aimed at knowing the effect of cooperative learning with jigsaw and flashcard on student’s achievement in fungi material for grade X SMA Negeri 1 Sajad. The research was Quasi Experimental Design with Non-Equivalent Control Group Design. The population of the study was two classes of grade X where grade XA was as experimental group and grade XB was as control group, with a sampling technique of saturated sampling. The instrument used multiple questions consisting 20 questions. According to data analysis result, the average score of posttest in experimental group was 17,82 and in control group was 14,89. Based on U Mann Whitney test, Zcount<-Ztable (-4,01<-1,96) showing that there was significant difference between student’s achievement using cooperative learning with jigsaw and flashcard and student’s achievement using conventional learning. Effect size score was 2,23 which is high, and gave effect by 48,71%.  Keyword: Jigsaw with a  Flashcard, Achievement, Fungi Material